2022
DOI: 10.3389/fonc.2022.859247
|View full text |Cite
|
Sign up to set email alerts
|

GFAPδ: A Promising Biomarker and Therapeutic Target in Glioblastoma

Abstract: GFAPδ, the delta isoform of the glial fibrillary acidic protein, is mainly expressed in the subventricular zone of the brain, together with other neural stem cell markers like nestin. The authors of this paper were among the first that described in detail the expression of GFAPδ and its correlation with malignancy and invasiveness in cerebral astrocytoma. Later, several papers confirmed these findings, showing that the alternative splice variant GFAPδ is overexpressed in glioblastoma (CNS WHO grade 4) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Of note, VEGF-A had the greatest increase in signal of all aptamers elevated with progression through bevacizumab (14.45x), consistent with its relevance to blood-brain barrier disruption in HGGs( 45, 46 ) in the setting of failed radiographic response to this anti-VEGF-A antibody ( Figure 4A) . GFAP was also evaluated as a previously proposed biomarker of GBM( 4749 ) and one of the top proteins that increased with progression through bevacizumab (3.59x). However, unlike BCAN, both VEGF-A and GFAP did not increase with progression through lomustine (1.03x and 0.63x, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, VEGF-A had the greatest increase in signal of all aptamers elevated with progression through bevacizumab (14.45x), consistent with its relevance to blood-brain barrier disruption in HGGs( 45, 46 ) in the setting of failed radiographic response to this anti-VEGF-A antibody ( Figure 4A) . GFAP was also evaluated as a previously proposed biomarker of GBM( 4749 ) and one of the top proteins that increased with progression through bevacizumab (3.59x). However, unlike BCAN, both VEGF-A and GFAP did not increase with progression through lomustine (1.03x and 0.63x, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…GFAP overexpression in GBM is frequently associated with blood–brain barrier disruption, and it is commonly found in patients’ serum as a biomarker for gliomas ( Yadav et al, 2022 ; Ghorbani et al, 2023 ). Alternative GFAP isoforms produced by alternative splicing have recently attracted attention for biomarker identification ( Radu et al, 2022 ). It has been shown that GFAP splice variant isoform ratios modulate glioma cell invasion, cytoskeleton dynamic, and organization ( Moeton et al, 2016 ; Stassen et al, 2017 ; van Bodegraven et al, 2019c ; Uceda-Castro et al, 2022 ; van Asperen et al, 2022 ), suggesting that GFAP is not only a passive viewer in GBM but could also play an active role and highlight the correlation between GFAP and cytoskeleton remodeling in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is a glial fibrillary acidic protein that is a promising biomarker and therapeutic target in glioblastoma ( 69 ) and other cancers ( 70 , 71 ); however, its role in prostate cancer has not been fully explored. One of the bioinformatics investigations nominated GFAP as a potential regulator of immune phenotypes in prostate cancer ( 72 ), yet its role in prostate cancer progression provides a new exciting avenue for further investigation, especially in combination with GADD45B, STAT3, and GFAP (and, potentially, FOXM1).…”
Section: Discussionmentioning
confidence: 99%